Kelayakan Bisnis Penyewaan Lighting Untuk Stasiun Televisi - Nugroho, Ig. Joko Adi; Suwandi, Suwandi (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This researched a business plan with the title “Lighting Equipment Rental Business for Television Station”. The objective of this project is to find out how beneficial the profit prospect of such business or lighting rental service business is. Service which is offered is the solution to television station’s demand for providing equipment for a program production. The Method instrument utilized to make the analysis of this business profitability is SWOT analysis, Canvas Model Business analysis and financial report projection analysis based on the logical assumption according to the real condition. The measurement to determine this business profit prospect is based on the capital repayment period and the expected profit projection. At the end of this research, it is generated an illustration explaining that the capital repayment can be made within 12 (twelve) months, so at the thirteenth (13th) month and the following months the profit gained.